1993
DOI: 10.1002/j.1460-2075.1993.tb06029.x
|View full text |Cite
|
Sign up to set email alerts
|

A cooperative interaction between NF-kappa B and Sp1 is required for HIV-1 enhancer activation.

Abstract: The human immunodeficiency virus (HIV‐1) long terminal repeat (LTR) contains two binding sites for NF‐kappa B in close proximity to three binding sites for the constitutive transcription factor, Sp1. Previously, stimulation of the HIV enhancer in response to mitogens has been attributed to the binding of NF‐kappa B to the viral enhancer. In this report, we show that the binding of NF‐kappa B is not by itself sufficient to induce HIV gene expression. Instead, a protein‐protein interaction must occur between NF‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
312
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 455 publications
(335 citation statements)
references
References 55 publications
18
312
3
Order By: Relevance
“…Therefore, we also tested the potential transcriptional leakage of the NF-kB-CEA enhancer -promoter system. In agreement with a previous report (Perkins et al, 1993), the NF-kB-binding sites by itself, as an enhancer element, only possessed very low transcriptional activity. The transcriptional activity in cancer cell lines was highly increased by the combination of kB4 and CEA promoter and meanwhile the cancer-targeting specificity was still remained ( Figure 3A and C and Table 1).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, we also tested the potential transcriptional leakage of the NF-kB-CEA enhancer -promoter system. In agreement with a previous report (Perkins et al, 1993), the NF-kB-binding sites by itself, as an enhancer element, only possessed very low transcriptional activity. The transcriptional activity in cancer cell lines was highly increased by the combination of kB4 and CEA promoter and meanwhile the cancer-targeting specificity was still remained ( Figure 3A and C and Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…Mutation of the adjacent kB and Sp1 DNA-binding sites completely abolishes the phorbol myristate acetate inducible transcriptional activity (Perkins et al, 1993). It was also reported that an Sp1-dependent promoter is distantly enhanced by an NF-kB enhancer (Teferedegne et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Such cooperativity has recently been described by Perkins et al (1993), who demonstrated that activation of the HIV-1 LTR depends on an interaction between p65 and Sp-1. Transactivation of the wt1 promoter is also positively regulated by Sp-1 (Cohen et al, 1997;Ho man et al, 1993).…”
Section: Discussionmentioning
confidence: 60%